Throwing the dart blind-folded: comparison of computed tomography versus magnetic resonance imaging-guided brachytherapy for cervical cancer with regard to dose received by the ‘actual’ targets and organs at risk - Yip, Winnie Wing Ling; Wong, Joyce Siu Yu; Lee, Venus Wan Yan; Wong, Frank Chi Sing; Tung, Stewart Yuk (Journal of Contemporary Brachytherapy, 2017)
Purpose : Computed tomography (CT) is inferior to magnetic resonance imaging (MRI) in cervical tumor delineation, but similar in identification of organs at risk (OAR). The trend to over-estimate high-risk and low-risk clinical target volume (HRCTV, IRCTV) on CT can lead to under-estimation of dose received by 90% (D 90 ) of the ‘actual’ CTV. This study aims to evaluate whether CT-guided planning delivers adequate dose to the ‘actual’ targets while spares the OAR similarly. Material and methods : MRI-guided high-dose-rate image-guided brachytherapy (IGBT) was performed in 11 patients. The pre-brachytherapy CTs were retrospectively contoured to generate CT-guided plans. MRI-based contours (HRCTV mri , IRCTV mri , bladder mri , rectum mri , and sigmoid mri ) were fused to CT plans for dosimetric comparison with MRI-guided plans. Paired 2-tailed t-test and Wilcoxon signed-rank test were used to analyze data. Results : 63.6% of CT plans achieved the HRCTV mri D 90 constraint (≥ 7.2 Gy in one fraction), compared with 90.9% for MRI plans. > 90% of both modalities achieved the OAR’s constraints (EMBRACE). The percentage of CT and MRI plans that achieved the aims (EMBRACE II) for bladder, rectum, and sigmoid were 36.4% vs. 81.8%, 63.6% vs. 63.6%, and 72.7% vs. 72.7%, respectively. There were no statistically significant differences in HRCTV mri D 90 , IRCTV mri D 90 , or dose received by the most exposed 2 cm3 (D 2cc ) of OARmri between the modalities. Excluding the CT plans not achieving HRCTV mri D 90 constraint, there were significant increase in bladder mri D 2cc , rectum mri D 2cc , and sigmoid mri D 2cc , compared with MRI plans (0.9 Gy/Fr, 95% CI 0.2-1.5, p = 0.018; 0.9 Gy/Fr, 95% CI 0.3-1.4, p = 0.009; 0.5 Gy/Fr, 95% CI 0.2-0.9, p = 0.027, respectively). Conclusions : MRI-based IGBT remains the gold standard. CT planning may compromise HRCTV mri D 90 or increase OARmriD 2cc , which could decrease local control or increase treatment toxicity.